Revealing enhanced dilution effect of conjugated polymers in partially miscible blends - Hongbo Chen; Ming Hu; Yuehua Zhao; Kaixuan Lyu; Yushuai Xu; Yuansheng Sun; Zhiyuan Xie; Jinying Huang; Dapeng Wang (Aggregate)
Abstract Recent experiments have shown that hole traps could be suppressed in polymer light‐emitting diodes under current stress by diluting the light‐emitting conjugated polymers within an “inert” large‐bandgap host material. However, it is unclear why there is an enhanced dilution effect in partially miscible blends rather than fully miscible blends, as intuition would suggest that better miscibility leads to better dilution. In this work, we propose a cascade analysis by combining multiple fluorescence microscopic techniques and all‐atom molecular dynamics simulations to study the solid‐to‐solid dilution of poly[2‐methoxy‐5‐(2‐ethylhexyloxy)‐1,4‐phenylenevinylene] (MEH‐PPV) in MEH‐PPV/polystyrene (PS) blends and MEH‐PPV/poly(vinylcarbazole) (PVK) blends. By varying the molecular weights of PS and PVK, we can regulate their miscibility with MEH‐PPV. The results corroborate that the dilution effect is enhanced in partially miscible blends rather than fully miscible ones. This is because, in partially miscible blends undergoing phase separation, the concentration of MEH‐PPV is notably decreased in the phase occupying the majority of the volume, leading to an overall greater dilution effect than in fully miscible blends. Moreover, MEH‐PPV could adopt the more extended conformation in the fully miscible blend, causing a shorter intermolecular distance to further undermine the dilution effect. These findings explain the seemingly counterintuitive more effective dilution effect observed in the recently reported partially miscible blends and provide guidance for further enhancing the performance of future generations of polymer light‐emitting diodes.